Anesthetic considerations in a patient of autosomal dominant polycystic kidney disease on hemodialysis for emergency cesarean section - Sarita D Fernandes; Deepa Suvarna (Wolters Kluwer Medknow Publications, 2011)
Renal disease, either preexisting or occurring during gestation may impair maternal and fetal health. A 35-year-old primigravida with autosomal dominant polycystic kidney disease on hemodialysis was scheduled for emergency cesarean section. She was managed successfully with low-dose intrathecal bupivacaine and fentanyl. In the case of pregnancy in such a patient, early involvement of the nephrologists along with the obstetrician can improve maternal and fetal outcome.